2014
DOI: 10.4103/0972-2327.128688
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenic networks and drug-resistant epilepsy: Present and future perspectives of epilepsy research-Utility for the epileptologist and the epilepsy surgeon

Abstract: A multidisciplinary approach is required to understand the complex intricacies of drug-resistant epilepsy (DRE). A challenge that neurosurgeons across the world face is accurate localization of epileptogenic zone. A significant number of patients who have undergone resective brain surgery for epilepsy still continue to have seizures. The reason behind this therapy resistance still eludes us. Thus to develop a cure for the difficult to treat epilepsy, we need to comprehensively study epileptogenesis. Till date,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
0
8
1
Order By: Relevance
“…Studies on recurrent seizures still have not been able to describe the etiology of epilepsy or explain the mechanism of seizure recurrence. 40 Even though our results appear to show that surgery provides a greater likelihood of a seizure-free status than nonsurgical treatment it does not guarantee that the seizure-free state can be maintained completely without using AEDs. It has been reported that “antiepileptic drug discontinuation is associated with a seizure recurrence in 1 in 3 patients rendered seizure free by epilepsy surgery.”’ 41 Since the risk of seizure recurrence is beyond the scope of our meta-analysis, great caution should be used in interpreting our results when providing patients with consultation about postsurgical care.…”
Section: Discussioncontrasting
confidence: 59%
“…Studies on recurrent seizures still have not been able to describe the etiology of epilepsy or explain the mechanism of seizure recurrence. 40 Even though our results appear to show that surgery provides a greater likelihood of a seizure-free status than nonsurgical treatment it does not guarantee that the seizure-free state can be maintained completely without using AEDs. It has been reported that “antiepileptic drug discontinuation is associated with a seizure recurrence in 1 in 3 patients rendered seizure free by epilepsy surgery.”’ 41 Since the risk of seizure recurrence is beyond the scope of our meta-analysis, great caution should be used in interpreting our results when providing patients with consultation about postsurgical care.…”
Section: Discussioncontrasting
confidence: 59%
“…b CNPase staining versus Olig2 positive cells/mm2. Sector 1 indicates cases with reactive oligodendroglial hyperplasia and normal myelin content, sector 2 cases with normal myelin and oligodendrocyte numbers and sector 3 burnout of oligodendroglia either with normal myelin levels (3a) or with severe cell and myelin loss (3b).…”
Section: Resultsmentioning
confidence: 99%
“…Although about two‐third of all epilepsy patients respond well to medical treatment with antiepileptic drugs (AEDs), 30%–40% cases are, or become, drug‐resistant 18, 19. For about one third of these patients, epilepsy surgery is an effective alternative treatment option 2. For those who are not surgical candidates, including patients with impaired cortical development and associated myelin deficiencies, new treatment strategies are urgently needed and, therefore, studies attempting to uncover the molecular basis of epileptic seizures and epileptogenesis or detect key targets for new therapies are of crucial importance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is believed that the initiation and propagation of paroxysmal discharges involve: The ability of a group of neurons to generate discharges; an excitatory glutamatergic system capacity, especially by the activation of N -methyl- d -aspartate (NMDA), which amplifies the signal and facilitates the generation of excitatory postsynaptic potentials (EPSPs); and the inhibitory GABAergic system capacity to regulate NMDA receptor activation to prevent the genesis of intracerebral transmission and control its spread via the generation of inhibitory postsynaptic potentials (IPSPs) [ 74 , 75 , 76 , 77 ].…”
Section: Epilepsy and Nrf2mentioning
confidence: 99%